2022
DOI: 10.3390/ijms23084112
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Expansion, and Evolution Analysis of Homeobox Gene Family Reveals TALE Genes Important for Secondary Cell Wall Biosynthesis in Moso Bamboo (Phyllostachys edulis)

Abstract: The TALE gene family is a subfamily of the homeobox gene family and has been implicated in regulating plant secondary growth. However, reports about the evolutionary history and function of the TALE gene family in bamboo are limited. Here, the homeobox gene families of moso bamboo Olyra latifolia and Bonia amplexicaulis were identified and compared. Many duplication events and obvious expansions were found in the TALE family of woody bamboo. PhTALEs were found to have high syntenies with TALE genes in rice. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…For example, Que. et al found that the TALE genes of Moso Bamboo and the TALE genes of rice have a high collinearity relationship (Que et al, 2022). In this study, we used the inter-species collinearity analysis to study the collinearity of TALE genes between P. mume and four other Prunus species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Que. et al found that the TALE genes of Moso Bamboo and the TALE genes of rice have a high collinearity relationship (Que et al, 2022). In this study, we used the inter-species collinearity analysis to study the collinearity of TALE genes between P. mume and four other Prunus species.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that evolution caused by gene duplication events is prevalent in angiosperms. For example, there is obvious expansion phenomenon in woody bamboo TALE gene family, which is caused by many duplication events (Que et al, 2022). Whole-genome duplication events occurred in G. raimondii and G. arboretum (Huang et al, 2020), and there were 34 gene pairs with fragment duplication in the TALE genes of G. hirsutum obtained by crossing the above two species, and also selected by purification (Zhang et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a limited number of studies have delved into the downstream targets of KNOX genes. KNOX is a TF and has been shown to modulate hormone levels, particularly cytokinin and auxin [23][24][25], to inhibit gibberellin synthesis [26], and to participate in secondary cell wall formation [27]. Consequently, KNOX genes emerge as pivotal contributors to plant growth and development [28].…”
Section: Introductionmentioning
confidence: 99%